METHODS OF GROWING DAIKON SEEDS IN UZBEKISTAN - Akramov U.; Sadriddinov F. (European Science Publishing, 2024)
Results of comparison of efficacy annual without relocate and two-year-old relocate a method of cultivation of seeds are stated. It is proved, that in Uzbekistan seeds of daikon can be cultivated to both methods. The greatest seed yield from unit of the area is formed at use of queen cells from sowing on July, 30th - on August, 10th.
Keywords: daikon, root crop, seeds, leaves, sowing dates, seed yield.